2002
DOI: 10.1021/ma001523u
|View full text |Cite
|
Sign up to set email alerts
|

High Glass Transitions of New Polyamides, Polyimides, and Poly(amide−imide)s Containing a Triphenylamine Group:  Synthesis and Characterization

Abstract: A new triphenylamine-containing diamine monomer, 4,4′-diamino-3′′,4′′-dimethyltriphenylamine (DADT), was successfully synthesized by the cesium fluoride-mediated condensation of 3,4dimethylaniline with 4-fluoronitrobenzene, followed by reduction. The monomer was reacted with various aromatic dicarboxylic acids and tetracarboxylic dianhydrides to produce a series of novel polyamides and polyimides, respectively. A new triphenylamine-containing dicarboxylic acid monomer, 4,4′-trimellitimido-3′′,4′′-dimethyltriph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
133
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(134 citation statements)
references
References 33 publications
1
133
0
Order By: Relevance
“…As expected, C-F multiple stretching absorptions were also measured at 1250 and 1145 cm À1 , respectively. Figure 1 shows a representative 1 H NMR spectrum of the fluorinated aromatic polyimide (PIEI-c) in DMSO-d 6 , in which it can be seen that all of the aromatic protons appeared in the region of 6.70-8.40 ppm and of the N-H protons of imidazol ring at 13.50 ppm.…”
Section: Pieis Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, C-F multiple stretching absorptions were also measured at 1250 and 1145 cm À1 , respectively. Figure 1 shows a representative 1 H NMR spectrum of the fluorinated aromatic polyimide (PIEI-c) in DMSO-d 6 , in which it can be seen that all of the aromatic protons appeared in the region of 6.70-8.40 ppm and of the N-H protons of imidazol ring at 13.50 ppm.…”
Section: Pieis Synthesis and Characterizationmentioning
confidence: 99%
“…In order to meet these requirements, structural modifications of these polymers often become essential. Therefore, considerable efforts have been made in recent years to develop highly optical transparent, low dielectric constant, and low refractive index aromatic polyimides with good processability by the incorporation of flexible linkages, [4,5] bulky pendant groups [6][7][8], and noncoplanar biphenylene moieties [9,10] into the polymer backbones. It has been observed that introduction of fluorinated substituents can impart many of these desirable properties to the polymers, making them suitable for a much wider range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…FTIR spectra of PI showed characteristic imide bands at 1780 and 1716 cm -1 (C=O stretching), 1355 cm -1 (C-N stretching), 832 and 716 cm -1 (C=O asymmetric stretching). An absorption at 1440-1660 cm -1 corresponding to the schiff base group (-CH=N-) is observed [8][9][10]. The thermal properties of the polyimides were evaluated by differential scanning calorimetry (DSC) ( Figure 4.…”
Section: Characterization Of the Pimentioning
confidence: 99%
“…Polyimides have been especially used widely in microelectronic, film, adhesive and membrane industry [3][4][5][6][7] due to these prior properties. Recently significant synthetic effort has been centered on improving processability and solubility through the synthesis of new diamine or dianhydride monomers [8][9][10]. In recent years, many polymers including conducting and nonconducting ones have been widely used for immobilization of enzymes at electrode surface [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much research effort has been concentrated on design and preparation of organosoluble polyimides without deterioration of their attractive properties. Some of the approaches to soluble polyimides are introduction of flexible linkages [4,5], bulky lateral substituents [6][7][8][9][10][11][12], noncoplanar [13][14][15][16][17][18][19], kinked [20][21][22][23][24][25] or alicyclic structures [26][27][28][29][30]. Among them, introduction of 2,2 -disubstituted twisted biphenyl structures into polyimide backbones was considered as one of the successful approaches.…”
Section: Introductionmentioning
confidence: 99%